Cellular Immunogenicity of Novel Gene Immunogens in Mice Monitored by in Vivo Imaging - Elizaveta Starodubova; Olga Krotova; David Hallengärd; Yulia Kuzmenko; Gunnel Engström; Diana Legzdina; Oleg Latyshev; Olesja Eliseeva; Anna Karin Maltais; Vera Tunitskaya; Vadim Karpov; Andreas Bråve; et al. (Molecular Imaging)
The efficient cell-mediated immune response clears cells expressing deoxyribonucleic acid (DNA) immunogens, but there are no methods to monitor this in vivo. We hypothesized that immune-mediated clearance can be monitored in vivo if DNA immunogens are coexpressed with reporter(s). To test this, we designed genes encoding human immunodeficiency virus 1 (HIV-1) reverse transcriptase (RT) fused via its N- or C-terminus to 30–amino acid-long Gly-Ala-repeat of Epstein-Barr virus nuclear antigen 1 or via the N-terminus to the transport signal of invariant chain/Ii or inserted between the cytoplasmic and luminal domains of lysosome-associated membrane protein I (LAMP). DNA immunogens mixed with luciferase gene were injected into BALB/c mice with subsequent electroporation. Reporter expression seen as luminescence was monitored by in vivo imaging. When luminescence faded, mice were sacrificed, and their splenocytes were stimulated with RT-derived antigens. Fading of luminescence correlated with the RT-specific secretion of interferon-γ and interleukin-2. Both immune and in vivo imaging techniques concordantly demonstrated an enhanced immunogenicity of RT-LAMP and of the N-terminal Gly-Ala-RT fusion genes. In vivo imaging performed as an animal-sparing method to estimate the overall performance of DNA immunogens, predicting it early in the experiment. So far, in vivo imaging cannot be a substitute for conventional immune assays, but it is supplementary to them. Further experiments are needed to identify which arms of cellular immune response in vivo imaging monitors best.